Pengembangan Potensi Pertanian dan Kesenian Desa Gotakan, Kapanewon Panjatan, Kabupaten Kulon Progo - Mayasari, Agatha (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
In KKN 80 UAJY, Group 94’s designated KKN location is located in Gotakan Village. Gotakan is one of the villages located in Panjatan District, Kulon Progo Regency, Special Region of Yogyakarta. The group programs that must be carried out are; to seek the Potential of the Village (Potensi Desa) and to make Pocket Books (Buku Saku) out of the village’s potential. In working on the two group programs, Group 94 collected data through the website. From the data collected, Group 94 saw the phenomena or problems faced by Gotakan Village. For the village's potential, there are two potentials, which are potentials in the arts and agriculture. The potentials in the arts sector are in the form of kenthongan, jathilan, and macapat; as well as the potentials for agriculture are shallots and coconuts. Looking at the potential of the village, problems were found, these problems are the lack of art preservation and product development of the village’s agricultural products. Therefore, Group 94 suggested the people of Gotakan to be able to better preserve their arts and develop their agricultural products. Regarding the development of agricultural products, Group 94 has made a pocket book containing coconut processing into coconut jam and gandos cake.